KEANEKARAGAMAN JENIS TUMBUHAN OBAT DI HUTAN KEMASYARAKATAN KESATUAN PENGELOLAAN HUTAN UNIT XIV TOBA SAMOSIR - Julita Dewi Pratidini Limbong; Rahmawaty Rahmawaty; Yunus Afifuddin (Program studi Kehutanan USU, 2016)
Medicinal plant is one of non-timber forest products whose parts can be used for medicine.This study analyzed the diversity of medicinal plants species in Community Forest (Hutan Kemasyarakatan) at Toba Samosir Forest Management Unit (KPH Unit XIV Toba Samosir). This study was conducted in February to May 2015 in Ajibata Sub-District, Toba Samosir District. Surveys (systematic random sampling with random start method) were conducted within the Community Forest. Senduduk buluh (Clidemia hirta) was the most abundant species which were found (12.09%) followed by putri malu (Mimosa pudica) (0.08%) and jahe (Zingiber officinale) (0.07%) of the total of medicinal plants in Community Forest. Species diversity in the community forest could be classified as high. therefore, the preservation of medicinal plant species in this community forests need to be maintained and enhanced for the benefit of community.Keywords: Community forest, Forest Management Unit, medicinal plant , Toba Samosi